Morphologic and histological characterization of root apex of avocado rootstocks and its resistance to soil adverse factors (Bioagro, 2018)
The root apex is essential in the relationships that it has with the soil conditions. Therefore, a root morphological and anatomical study was carried out in avocado clonal genotypes for groping, and to determinate characteristics that could correspond to adaptation to biotic or abiotic adverse soil factors. Clonal 90 day-old plants were used, in a randomized design with tree replicates, where 32 characteristics of root apex, tissue, cap and cells were measured. From 12 selected variables, a grouping analysis was carried out that generated a hierarchical dendrogram and suggested the formation of four groups, that were corroborated by a canonical discriminative analysis. The cap area, distance between root apex and vascular cylinder and cortex width showed influence on grouping. The Group 1 was characterized by a medium thin apex, but with close angle, Group 2 had thick apex with close angle, Group 3 thin and slightly flat apex, and Group 4 thick rounded apex. There were no clear genotypes grouping according to their adaptation to adverse soil conditions, based on the characteristics supposed to be associated to root protection.